Analysis of the Geoelectric Field in Sweden Over Solar Cycles 23 and 24: Spatial and Temporal Variability During Strong GIC Events - V. Lanabere; A. P. Dimmock; L. Rosenqvist; L. Juusola; A. Viljanen; A. Johlander; E. Odelstad (Space Weather)
Abstract Geomagnetic storms can produce large perturbations on the Earth magnetic field. Through complex magnetosphere‐ionosphere coupling, the geoelectric field (E) and geomagnetic field (B) are highly perturbed. The E is the physical driver of geomagnetically induced currents. However, a statistical study of the E in Sweden has never been done before. We combined geomagnetic data from the International Monitor for Auroral Geomagnetic Effects network in Northern Europe with a 3‐D structure of Earth's electrical conductivity in Sweden as the input of a 1‐D model to compute the E between 2000 and 2018. Northwestern Sweden presents statistically larger E magnitudes due to larger |dB/dt| variations in the north than in the south of Sweden and relative lower conductivity in the west compared to central and eastern Sweden. In contrast, the 15 strongest daily maximum |E| events present more frequently a maximum magnitude in central Sweden (62.25°N) and their relative strengths are not the same for all latitudes. These results highlight the different regional response to geomagnetic storms, which can be related to ground conductivity variability and the complex magnetosphere‐ionosphere coupling mechanisms.